Effect of moisture-stress and phosphorus levels on the performance of gram (Cicer arietinum) - CHAVAN, L S; PATIL, B P (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during the winter season of 1991-92 and 1992-93 to study the effect of moisturestress and phosphorus levels on the performance of ’Vishwas’ gram or chickpea (Cicer arietinum L.) in a split-plot design. Six levels of irrigation (3 irrigations at 25, 50 and 75 days after sowing, 4 irrigations at 15, 30, 45 and 75 days, 2 irrigations at 25 and 50 days, 4 irrigations at 15, 30, 50 and 75 days, 2 irrigations at 45 and 75 days and 1 irrigations . at 25 days), at different growth stages of gram were in main plots and 4 levels of phosphorus (0, 11,22 and 33 kg P/ha) in subplots. Integrated effect of stress-free conditions due to 3 irrigations at 25, 50 and 75 days after sowing with P 22 kg/ha did not reduce seed yield (2.19 tonnes/ha) of gram significantly than the same moisture level with the P 33 kg/ha (2.25 tonnes/ha). Imposing water-stress throughout and providing stress relief only once at 25 days after sowing proved significantly superior (1.39 tonnes/ha) to that providing stress relief twice at 45 and 75 days after sowing (1.16 tonnes/ ha) in respect of seed yield. Relief of moisture-stress twice at 25 and 50 days after sowing was equally effective (1.70 tonnes/ha) to stress relief 4 times at 15, 30,45 and 75 days after sowing (1.74 tonnes/ha) as well as at 15,30,50 and 75 days after sowing (1.67 tonneslha) in respect of seed yield. The P stress from 22 kg/ha (1.75 tonnes/ha) to 11 kg/ha reduced the gram yield significantly (1.59 tonnes/ha). Â